Měření a hodnocení výkonnosti podniku - Filouš, David (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Tato bakalářská práce je zaměřena na měření a hodnocení finanční situace podniku GPD, a. s. Je za měřena na roky 2018, 2019, 2020, 2021 a 2022. Skládá se ze 3 částí. První část bakalářské práce je zaměřena na teoretické aspekty finanční analýzy. V druhé části je představen podnik, který bude analyzován a také jeho konkurence. Poslední část je zaměřena na návrhy, které by mohly zlepšit finanční situaci podniku.

This bachelor thesis is focused on the measurement and evaluation of the financial situation of GPD, Inc. It is measured for the years 2018, 2019, 2020, 2021 and 2022. It consists of 3 parts. The first part of the bachelor thesis focuses on the theoretical aspects of financial analysis. The second part introduces the company that will be analyzed and also its competitors. The last part focuses on suggestions that could improve the financial situation of the company.
Measurement and Evaluation of Business Performance
Keywords: Finanční analýza; rozvaha; výkaz zisku a ztrát; cash flow; likvidita; rentabilita; Financial analysis; balance sheet; profit and loss statement; cash flow; liquidity; profitability